Performance analysis of handball goalkeepers at the different world championships - Parthipan, S.; Kalidasan, R. (Dogo Rangsang Research Journal, 2022)
The objective of this study was to analysis Handball Goalkeeper"s Performance analysis. The selected subject was taken from 2015 France Goalkeeper (2015FG), 2015 Qatar Goalkeeper (2015QG), 2017 Norway Goalkeeper (2017NG), 2017 Croatia Goalkeeper (2017CG), 2019 Denmark Goalkeeper (2019DG), 2019 Norway Goalkeeper (2019NG), 2021 Denmark Goalkeeper (2021DG) and 2021 Sweden Goalkeeper (2021SG) Handball World Championship final match videos were using the study total of eight goalkeepers was taken into the study. Variables would be using Longomatch video analyzing software. The selected variables namely basic notational analysis Types of Shots: (6-MLS) 6-Metre Line Shots successful /unsuccessful, (9-MLS) 9- Metre Line Shots successful /unsuccessful, (7-MT) 7- Metre Throws (Penalty) successful /unsuccessful, (LRS) Long Range Shots away from 9- Metre Line successful /unsuccessful, (FBS) Fast Break Shots successful /unsuccessful, (RS) Running Shots successful /unsuccessful, (BS) Back Shots successful /unsuccessful, (BBS) Blocked Ball Shots successful /unsuccessful. The successful is the Goalkeeper successful save the shots is save point and the Goalkeeper miss the shots is called as unsuccessful is shot miss the point ( Milanovic, 2018). In the position phases of the game, situational activity indicators have been analysis within 5 playing positions in the position attack Playing Zone Wise Shot Analysis: (RW) Right Wing, (RB) Right Back, (CB) Centre Back, (LB) Left Back, (LW) Left Back the pivot player doesn't stay the one place so pivot player shots attempt time staying place covering the five-zone so don't give separate playing zone name (Foreti, 2013). Goal Post-Zone Wise Analysis: The handball goal post was divided into Nine zones (Z -1TRC) Zone-1 Top Right Centre, (Z-2TC) Zone-2 Top Centre, (Z-3TLC) Zone-3 Top Left Centre, (Z 4CR) Zone-4 Centre-Right, (Z-5CC) Zone-5 Centre Centre, (Z-6CL) Zone-6 Centre Left, (Z-7BRC) Zone-7 Bottom Right Corner, (Z-8BC) Zone-8 Bottom Centre, (Z-9BLC) Zone-9 Bottom Left Corner (YIANNAKOS, 2016). Data analysis performed using a simple calculation method was used.